Recontextualising Ece Temelkuran in the UK: A Paratextual Look at the English Translations of Her Works - (:unkn) unknown (ISTANBUL UNIV, FAC LETTERS, 2020)
Literary and non-literary works from Turkey have become more visible in the UK market through translations since the early 2000s. This increased interest in Turkish titles has been accompanied by the expectation from the authors to speak for their communities and represent their countries. Hence, translation has constituted a site of political signification in that Turkish authors'works have largely been discussed in view of the information and/or criticism they provide about their social and political contexts of origin. Following in the footsteps of the literature on the promotion and reception of Turkish authors in translation, this article examines the English translations of Ece Temelkuran's selected works with a focus on how they were presented in the UK. Specifically, it will offer a descriptive analysis of the paratextual elements of Turkey: The insane and The Melancholy and Women Who Blow on Knots. In doing so, the article will focus mainly on the front and back covers, translated titles, visuals and blurbs of the selected books. This study shows that the translator's work is more likely to be recognised when a Turkish title is selected for translation for its literary success in its country of origin rather than for the timeliness of its political commentary. In parallel, it will be argued that the selection of an author's books for publication in the UK based on their literary merit provides more room for that author to release the burden of political signification.
Keywords: Paratexts; book covers; translated Turkish literature; translations into English; Ece Temelkuran; WOMEN